(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This article seeks to analyze the role of anthropology as a scientific and methodological tool for understanding social and political movements in modern societies. It employs the analytical and theoretical tools developed by cultural and social anthropology to understand collective behavior and the symbolic and cultural meanings that motivate individuals and groups in the political sphere. The article focuses on qualitative approaches, particularly participant observation, in-depth interviews, and discourse analysis, to deconstruct political phenomena from a grassroots perspective, rather than solely through the lens of the state or official institutions. The article also examines the traditional methods adopted by political science to interpret social movements, revealing their limitations in recognizing the cultural, religious, and identity dimensions that fuel many of these movements, particularly in popular Arab societies. It demonstrates how the anthropological approach can uncover the hidden structures and symbolic meanings underlying protests and demands for justice and equality. The article emphasizes that anthropology not only provides tools for understanding the deep local context of political movements, but also helps analyze the complex interplay between culture, politics, economics, religion, and identity, providing a more comprehensive and in-depth view of contemporary social and political transformations. Accordingly, the article highlights the need to enhance the integration of political science and anthropology to develop interpretive models that are more sensitive to diverse cultural and historical contexts.